Barreiras e facilitadores da adesão ao tratamento de tuberculose em crianças e adolescentes - Marina Mariano Rodrigues Santos; Bruna Villela Martins Costa; Maria Clara Bomfim Rodrigues; Claudete Araújo Cardoso (Sociedade Brasileira de Pediatria, 2024)
INTRODUCTION: Tuberculosis (TB), an infectious and contagious disease, requires prolonged treatment and usually affects socially vulnerable patients, which increases the risk of abandonment during its course. Children and adolescents are susceptible to this infection, requiring adequate treatment for a favorable clinical outcome. It is known that adherence to TB treatment is the main obstacle to cure the disease, and it is important to know the factors that could influence this adherence. The aim of this review is to analyze the factors that interfere with adherence to TB treatment in children and adolescents. METHODS: This systematic literature review was conducted by searching the descriptors Tuberculosis (OR Tuberculosis) AND Adherence (OR Adhesion) in the PubMed, Scielo and Lilacs databases. Articles about the adherence of children and adolescents to TB treatment were included. Duplicates were excluded. The selection of articles for review was conducted in the following steps: analysis of titles, reading of abstracts and full articles. At the end of the selection, 28 articles were reviewed. RESULTS: The main barriers to adherence to TB treatment were: prolonged treatment time, adverse effects, caregivers lack of knowledge about the disease and latent infection and socioeconomic status. The main facilitators were: shorter treatment, directly observed, financial support and advice from patients and caregivers. HIV-TB co-infection can increase adherence due to routine medication intake, or decrease due to the increase in adverse effects. CONCLUSION: The acknowledgement of the facilitators and barriers to adherence allows directing the necessary efforts to promote best response to TB treatment.